Symbolic Islamo-European Encounter in Prosody: Muwashshahat, Azjal and the Catalan Troubadours - Sanaullah, Muhammad (Islamic Studies, 2010)
The aa dda a prosodic trajectory of Muwashshahat and Azjal travelling from Andalusia to Germany via Provence, Sicily and Italian cities and culminating into the domnei poetics of the troubadours, the trouveres, the Italian trovatori, the trobairitz and the German Minnesingers calls for whisking out the medieval Arab-Romance mignonette that posited itself within the modern poetics and music. Europe had waited till the twelfth century CE to be initiated into the path of love-poetry as psychic posture and a new poetic fashion, owing much to the troubadours. The courtly ideas in Europe owed greatly to the courtly ideas in Provence which were derived from the courts of Reyes de Taifa (1031–1095) of Muslim Spain (711–1492). The imprints ofthe hybrid Andalusian Arab-Romancephilology and scansion system, best represented by the Washshahun (Ibn Quzmun, Ibn Sahl, Ibn al-Shushtiri, Ibn al-Labbanah, Ibn Zamrak, ‘Ubadat al-Qazzaz, Ibn ‘Arabi and others), are to be easily found in the cansoni of respectable Catalan poets in Spain, Galicia and Midi like Alphonso El Sabio, William XI of Aquitaine,Marcabru, Jaufre Rudel, Ruben Dario, Juan Ruiz and others. The troubadours’ sensibility to the Andalusian poetic apogee in search of dulcedo or sweetness outside Boethius, Cicero and Horace warranted a practice and emulation of a poetic module embodying love, virtue and security is traced outside Latinity, in theneighbourhood, especially in the Mozarabic Spain.